KAJIAN POPULASI DAN HABITAT BURUNG ENDEMIK DAN SEBARAN TERBATAS DI TAMAN WISATA ALAM CAMPLONG - Blasius Paga; Fransiskus X. Dako; Yudhistira A. N. Rua Ora (Partner, 2008)
Study on Population and Habitat of Endemik and Restricted Range Birds in Camplong Natural Recreation Park. This research took place in Camplong Natural Recreation Park from March to October 2007, in order to estimate the population density and size of those birds, and to study their habitat, comprising their habitat composition and vegetation structure, stratification and altitude. The primary data were obtained by direct observation and interview. Data population was obtained by using Variable Circular Plot method ((Buckland et al., 1993; Kartono, 2000). Identification of birds and vegetation used literature study. The results showed that there were 45 species of birds recorded in the Park. Among them, 6 birds were Timor’s endemik, 18 were Nusa Tenggara endemik, and 24 were restricted range species. During one year, 9 restricted range birds were missing. The highest population density of the Bird was Meliphaga reticulata (27,500/km2, ranges from 28.979 to 26.021/km2), and followed by Gerygone innornata (25.000/km2, ranges from 24.572 to 25.428/km2). On the other hand, the lowest density of the bird was Heleia muelleri, one of the six endemik birds of Timor (0.833 /km2, ranges from 0.729 to 0.938 /km2. Vegetation in Camplong Natural Recreation Park recorded in various life stages showed that there were 63 trees, 27 poles, 28 saplings and 22 seedlings. Overall, there were 90 species of trees recorded in all strata. The highest Important Index Value (INP) of tree is taduk (30.6686 %), and generally tree species with the highest INP comprises A to B strata with canopy may reach 30 – 40 m in height. escortcity.co.nz Pole is dominated by keolnasa (INP 68.8674 %). Sapling is also dominated by keolnasa (INP 75.2536 %), while seedling is dominated by Chromonela odorata, with INP reaching to 91.1337 %. Keywords: birds, Camplong natural recreation park